Krapcho Dealkoxycarbonylation Strategy of Ethyl Cyanoacetate for the Synthesis of 3-Hydroxy-3-cyanomethyl-2-oxindoles and 3,3′-Dicyanomethyl-2-oxindoles in a Reaction with Isatin - R., Chandran; Tiwari, Keshri Nath (Synthesis, 2020)
A new strategy for the synthesis of 3-hydroxy-3-cyanomethyl-2-oxindoles and 3,3′-dicyanomethyl-2-oxindoles in a reaction of isatin with ethyl cyanoacetate by Krapcho dealkoxycarbonylation reaction in aqueous media is demonstrated. The reaction provides an easy access to synthetically and medicinally valuable oxindole alkylnitriles in good to very good yields. Wider substrate scope and operationally simple experimental procedures are highlighted features of the developed protocol. Based on control experiments, a plausible mechanism of reaction and synergistic effect of water is also rationalized.
Keywords: aldol-type cyanomethylation; dealkoxycarbonylation; 3,3′-disubstituted oxindole; ethyl cyanoacetate; isatin